Bolger, Dermot. The Passion of Jerome. London: Methuen, 1999. 89 pp. - Kurdi, Mária (FOCUS: Papers in English Literary and Cultural Studies, 2002)
Dermot Bolger’s career as playwright started with the works later published in a volume titled A Dublin Quartet (1992), which can best be described in terms of variations on the theme of quest, offering a sense ofhome, home country and identity as fluid and protean. Following the measurable success of this debut, April Bright (1995) broke a new path by channeling the search into a more personal direction. The Passion of Jerome (1999), written by Bolger during his writer-in-residence period at the Abbey Theatre, continues along largely the same line, having its protagonist encounter the ghosts of the past impinging on the present of contemporary Celtic Tiger Dublin life fractured by significant social differences. It stages the unfolding crisis and subsequent transformation of forty-year-old Jerome, a faithless Catholic who at first cynically labels himself as “an honest hypocrite”, and is shown involved in a vehement extramarital love affair with a much younger colleague his wife trusts as friend. Moreover, married to a rich Protestant woman he magines himself happy without kids, referring to them as mere “appendages”, and appears to feel comfortable enough amid his entangled relationships. The play depicts how this complacent enough mask gets fiercely punctured, revealing inner hollowness behind a web of delusions and lies.